Trends and predictors of opioid use after total knee and total hip arthroplasty. Issue 6 (June 2016) - Goesling, Jenna; Moser, Stephanie E.; Zaidi, Bilal; Hassett, Afton L.; Hilliard, Paul; Hallstrom, Brian; Clauw, Daniel J.; Brummett, Chad M.
Abstract : Abstract: Few studies have assessed postoperative trends in opioid cessation and predictors of persistent opioid use after total knee arthroplasty (TKA) and total hip arthroplasty (THA). Preoperatively, 574 TKA and THA patients completed validated, self-report measures of pain, functioning, and mood and were longitudinally assessed for 6 months after surgery. Among patients who were opioid naive the day of surgery, 8.2% of TKA and 4.3% of THA patients were using opioids at 6 months. In comparison, 53.3% of TKA and 34.7% of THA patients who reported opioid use the day of surgery continued to use opioids at 6 months. Patients taking >60 mg oral morphine equivalents preoperatively had an 80% likelihood of persistent use postoperatively. Day of surgery predictors for 6-month opioid use by opioid-naive patients included greater overall body pain ( P = 0.002), greater affected joint pain (knee/hip) ( P = 0.034), and greater catastrophizing ( P = 0.010). For both opioid-naive and opioid users on the day of surgery, decreases in overall body pain from baseline to 6 months were associated with decreased odds of being on opioids at 6 months (adjusted odds ratio [aOR] = 0.72, P = 0.050; aOR = 0.62, P = 0.001); however, change in affected joint pain (knee/hip) was not predictive of opioid use (aOR = 0.99, P = 0.939; aOR = 1.00, P = 0.963). In conclusion, many patients taking opioids before surgery continue to use opioids after arthroplasty and some opioid-naive patients remained on opioids; however, persistent opioid use was not associated with change in joint pain. Given the growing concerns about chronic opioid use, the reasons for persistent opioid use and perioperative prescribing of opioids deserve further study. Abstract : Supplemental Digital Content is Available in the Text.Many patients taking opioids before arthroplasty and some opioid-naive patients continued to use opioids postarthroplasty. Persistent use was not associated with changes in joint pain.